Creatividad en la expresión corporal para el desarrollo de las destrezas cognitivas de los estudiantes de 3º año de educación general básica de la Escuela Gloria Navarrete de Castro Provincia de Los Ríos cantón Babahoyo - Pazmiño Ribadeneira, Elvida Patricia (2019)
The purpose of this study is to emphasize the importance of the theme of Creativity in the corporal expression for the development of cognitive skills, to know the reason of the creativity of the human being, to differentiate the levels of the creative process, and above all, about the thought that creativity is an inherent intelligence resource of each human being, therefore its development is essential since one of the main objectives of the teacher is that the student is reflective and autonomous, obtaining a better development of their cognitive abilities. Creativity is the ability of the human being to create something of other ideas that are new and interesting, that is, the ability to analyze and evaluate new ideas, solving problems that arise during the life of the human being and the challenges that arise in the academic and daily. Creativity is necessary not only in school, but in all activities that people do, the school must be a fundamental pillar to enrich and encourage creativity in each of the students. Through this, the child develops the motivation, stores the greatest amount of information generating different alternatives of answers that must be novel.